CODE-MIXING AS AN ALTERNATIVE TO COMMUNICATION AT THE THAI TERTIARY CONTEXT AND BEYOND - Tassev, Valentin Valentinov (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2020)
The following study examines the use of code-mixing or the mixing of Thai and English in the process of communication mainly between Thais and non-Thais at the Thai tertiary context and beyond. This study suggests that code-mixing occurs as a result of the transfer of Thai socio-cultural norms and elements that intersect with the English language and characterize the emergence of a newly-nativized variety or norm of English used in Thailand. A recurring theme of this study is the idea that the status and nature of English in Thailand have been constantly changing and this trend largely concerns the communication mainly between Thais and non-Thais, as well as to some extent between Thais themselves and between non-Thais themselves, especially in the educational domain. In light of this, this study suggests that educators and educational policy-makers need to promote awareness of the evolution of English as a global language and implement practices and policies oriented towards teaching and assessing English from a more inclusive and pluralistic perspective, concerning both instructors and students of English in Thailand and beyond.